UNESCO biosphere reserves
1 online resource
Keywords: "UNESCO Biosphere Reserves are geographical regions of global socio-ecological significance. They are designated within UNESCO's Man and Biosphere Programme, and form an international, intergovernmental network that supports the aims of sustainability science. This book shows their global relevance and outlines lessons learned about biocultural diversity, sustainability, and society. This book will be of great interest to professionals engaged in conservation and sustainable development, NGOs, policy-makers and advanced students in environmental management, ecology, sustainability science, environmental anthropology and geography"--